Effect of blasting waste as an additive in bitumen mixtures - Saiful Hazman Mokhtar,; Ernie Binti Kulian @ Abd Karim,; Nur Hanani Daud, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The use of blasting waste in road pavement mixes is one of the new alternatives in Malaysia. Therefore, this study aimed to look at the potential of blasting waste as an additive in bitumen mixtures in road construction. Several percentages of blasting waste additive were studied, namely 0%, 5%, 10%, 15% and 17%. The parameter values of each of these mixtures were obtained through the Marshall test. A total of five sets of specimens were prepared for the Marshall test, with each set containing three samples. From the test result, all the percentages of blasting waste as an additive in the bitumen mixture passed the Public Works Department (Jabatan Kerja Raya or JKR) specifications. It was also concluded that 10% of blasting waste as an additive is the optimum value, with a stability value of 82.5kN as compared to the stability value of the control sample at 37.7kN. The flow and Marshall Quotient values for the 10% sample were 4mm and 20kN/mm, respectively. All values obtained from this study were in accordance with JKR specifications, indicating that blasting waste has great potential in improving the specification values of bitumen mixtures.